Characterization of Spinel-type LiAlxMn2-xO4 Prepared by Liquid-phase Combustion Synthesis - Chen, Mimi; Zhou, Xianyan; Su, Changwei; Xiang, Mingwu; Guo, Junming (Asian Journal of Chemistry, 2014)
LiAlxMn2-xO4 with submicron-sized particles were synthesized by liquid-phase combustion synthesis method at 500 °C for 3 h. LiNO3, Li(OAc)2·2H2O, Mn(NO3)2, Mn(OAc)2·4H2O and Al(NO3)3·9H2O were used as raw materials. The X-ray diffraction pattern of products suggested they included a less impurity of Mn3O4 and a main LiMn2O4 phase with a spinel structure except that LiAl0.08Mn1.92O4 had a single phase of LiMn2O4. Cycle performance revealed that Al doping samples (x £ 0.10) possessed higher initial discharge capacity. Moreover, capacity fading could be suppressed by doped-Al. Especially, LiAl0.08Mn1.92O4 exhibited the highest value of 116.4 mAh/g and the highest retention of 82.3 % after 40 cycles. The data of cycle voltammetry and electrochemical impedance spectrum (EIS) indicated that polarization and charge transfer impedances (Rct) of LiAlxMn2-xO4 were reduced by doped-Al, suggesting better reversiblities of Li+ insertion/extraction.